miRNA-29b Inhibits Prostate Tumor Growth and Induces Apoptosis by Increasing Bim Expression - Sur, Subhayan (Cells, 2019)
Prostate cancer is one of the most common cancers among men. Currently available therapies improve patient survival against local prostate cancer but have shown severe side effects. Advanced prostate cancer is still incurable. Studies have suggested the involvement of non-coding RNAs, especially micro-RNAs (miRNAs), in the regulation of multiple cellular events in cancer and thus several clinical trials are ongoing using miRNAs mimics or inhibitors. We previously demonstrated that miRNA-29b-3p (miR-29b) was downregulated in prostate cancer and that the overexpression of miR-29b limited prostate cancer metastasis. However, the therapeutic potential of the miR-29b against prostate cancer remains unknown. Here, we evaluated the therapeutic role of miR-29b in in vivo prostate tumors in a mouse model. Intratumoral injection of mimic miR-29b significantly inhibited prostate cancer xenograft tumor growth in nude mice. Subsequent study demonstrated that the overexpression of miR-29b reduced prostate cancer cell PC3 proliferation in a time dependent manner and induced cell death. Mechanistic study using a cancer pathway specific transcriptomic array revealed a significant overexpression of the pro-apoptotic gene BCL2L11 (Bim) in the miR-29b overexpressed PC3 cells, which was further verified in PC3 cells overexpressing miR-29b. We also observed a significant induction of Bim protein in miR-29b treated xenograft tumors. The induction of cytosolic accumulation of cytochrome C and PARP cleavage in miR-29b overexpressed PC3 cells was observed. Thus, our results suggest that miR-29b can be used as a potential molecule for prostate cancer therapy.